Trauma and The Gradual Triumph of the Black Feminist Voice in Alice Walker The Color Purple - Intissar ZAHAF, Amina GHADBANE (UNIVERSITY MOHAMED BOUDIAF - M’SILA, 2021)
ABSTRACT The present research focuses on how racism impacted the psychology of the American Black Women in Alice Walker’s novel “The Color Purple” .Walker’s novel represent the way Black women endured the double burden of being the subject of racism. Thus, the main aim of this study is to develop a strong understanding of the different crucial aspects that influenced the psychological side of the Black female. The study uses Black Feminist theory along with trauma theory to examine the black female harsh experiences in a society dominated by white supremacy and patriarchy. This literary piece also examines the healing process of the protagonist in Alice Walker's epistolary novel The Color Purple. Walker did not limit herself to describing the suffering of African-American women, but suggested a path to all women to get rid of the evils of patriarchy and sexism. The protagonist, Celie, changed her status as a female slave who has been sexually abused, and liberate herself financially, physically and spiritually. The good relationship of sisterhood with her sister Nettie along with writing letters helped Celie succeed in her journey towards healing and triumph.